2000
DOI: 10.1021/jp9940497
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between Li Atoms and HX (X = F, Cl) Molecules:  Semiempirical SCF MO and Matrix Isolation ESR Studies

Abstract: Examination of reaction between the Li atom and the HX (X ) F, Cl) molecule by a semiempirical molecular orbital method (AM1) revealed the spontaneous formation of the Li:HCl and Li:HF complexes with the respective heats of complexation of 75 and 84 kJ/mol. The calculations yielded totally different structures for the two complexes, however. In the Li:HCl complex, the unpaired electron is in the antibonding σ orbital of the H-Cl moiety and the elongated H-Cl is sided by the Li atom bearing a substantial positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…As stated above, our recent study of the reaction between the Li atom and the H-Cl molecule has revealed that the reaction commences with the attraction arising from the threeelectron bonding scheme between the unpaired electron of the Li atom and the lone pair electrons of the halogen atom and, when the energy level of the SOMO of the reacting system (given by the antibonding combination of the Li valence orbital and the halogen p orbital) crosses the level of the antibonding orbital of the H-Cl moiety, the unpaired electron migrates from the former to the latter. 9 In a separate, earlier matrix isolation ESR study, it has been shown that when an electron is added to TMO, the resulting anion has the ring-opened structure as shown below. 14 On the basis of these results, one may postulate that the insertion of an Al atom into the TMO ring occurs as follows.…”
Section: Computational Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As stated above, our recent study of the reaction between the Li atom and the H-Cl molecule has revealed that the reaction commences with the attraction arising from the threeelectron bonding scheme between the unpaired electron of the Li atom and the lone pair electrons of the halogen atom and, when the energy level of the SOMO of the reacting system (given by the antibonding combination of the Li valence orbital and the halogen p orbital) crosses the level of the antibonding orbital of the H-Cl moiety, the unpaired electron migrates from the former to the latter. 9 In a separate, earlier matrix isolation ESR study, it has been shown that when an electron is added to TMO, the resulting anion has the ring-opened structure as shown below. 14 On the basis of these results, one may postulate that the insertion of an Al atom into the TMO ring occurs as follows.…”
Section: Computational Resultsmentioning
confidence: 95%
“…The efficacy of a semiempirical SCF molecular orbital method (e.g., AM1) in elucidating the reaction process between a paramagnetic atom and a small molecule has been demonstrated in our recent study of the reaction between Li atoms and HX (X = F, Cl) molecules . The MO study predicted that the Li atom would approach the H−Cl (or F) molecule spontaneously driven by the three-electron bonding scheme between the Li unpaired electron and the lone pair electrons of the halogen atom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another slight rise in PE then opposes the decomposition of this intermediate into H + MH. In the analogous reaction with CH 4 (i.e., X ) CH 3 ), however, the progress of the reaction M ( 3 P)‚‚‚CH 4 f [CH 3 MH]* is inhibited by a substantial barrier attributable to steric factors. 47 For the reaction between a Group 12 metal atom and HCl, our calculations were unable to locate any minima for a complex formed between the metal atom in its 3 P 1 excited state and the HCl molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Although there exists, to our knowledge, no previous matrix-isolation study of the reaction between Zn or Cd atoms and HCl, several other metals have been investigated for their response to HCl. Thus, a more electropositive metal atom from Group 1 reacts to form the ion pair M + HCl - , which can be detected by its electron paramagnetic resonance (EPR) spectrum; this occurs spontaneously when M = K but only on irradiation when M = Na. , By contrast, Li reacts spontaneously to form a complex Li·HCl, also identified by its EPR spectrum; here the HCl is coordinated side on to the metal atom, which is estimated to bear a charge of +0.47 e . Insertion of the metal atom M into the H−Cl bond to form the metal hydride HMCl occurs with other metal atoms, notably Al, Fe, and Hg .…”
Section: Introductionmentioning
confidence: 99%